Oxidation state and halogen influence on the NHC-gold-halide-catalyzed cyclization of propargylic amides - Sargentoni, Nicola; Galassi, Rossana; Luciani, Lorenzo; Rominger, Frank; Rudolph, Matthias; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2024)
The homogeneously catalyzed cycloisomerization reaction of propargylic amides was tested as benchmark reaction for two homologous series of Au(I) and Au(III) complexes with NHC ligands. This reaction is known to afford either aromatic oxazoles or dihydrooxazoles, depending on the oxidation state of the applied gold catalysts. For this purpose, symmetric and unsymmetric NHC ligands with mixed alkyl or benzyl substituents (1,3-dimethyl-imidazolyl-2yl or 1-benzyl-3-methyl-imidazolyl-2-yl) and the corresponding Au(I) and Au(III) derivatives were prepared and characterized by analytical methods, IR and 1H and 13C NMR spectroscopies, and by X-ray diffraction methods. Ten NHC-gold(I) and NHC-gold(III) complexes were tested on the cyclization reactions by adding gold catalysts in the presence and absence of AgPF6. Noteworthy, only the 1-benzyl-3-methyl-gold(III) trichloride was able to give selectively the aromatic oxazole without the addition of the silver salt. Interestingly, on contrary to what is reported in the literature, the use of gold(I) or gold(III) complexes does not influence the chemoselectivity of the cyclization reaction, while the halide bound to the metal does. In this regard, a mechanism purposing the dihydrooxazole as an intermediate for the formation of aromatic oxazole is proposed.
Online verfügbar: 2. September 2024, Artikelversion: 14. Oktober 2024
Gesehen am 28.03.2025